2002-2015 yılları arasında Türkı̇ye’nı̇n İsraı̇l ı̇le tı̇carı̇ ı̇lı̇şkı̇lerı̇ ve ekonomı̇ polı̇tı̇k analı̇zı̇ - Göksu, Sedat (My University, 2017)
İsrail’in kurulduğu dönemden bu yana Türkiye ve İsrail arasındaki ilişkiler, inişli-çıkışlı bir şekilde olmuştur. ABSTRACT Since Israel was founded, relations between Turkey and Israel have been bumpy. The economic and political analysis of Turkey's commercial relations with Israel from 2002 to 2015 constitutes
Keywords: Dış ekonomik ilişkiler; economic crisis; Ekonomi politikası; Ekonomik analiz; Israel; İsrail; political analysis; Politik analiz; Tarih; Ticari ilişkiler; trade relations; Turkey; Türkiye